Evaluation Report on Comprehensive Arts Planning Program (CAPP) - Minnesota State Dept. of Education, St. Paul.; Minnesota State Dept. of Education, St. Paul. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
Comprehensive Arts Planning Program (CAPP) grants were awarded to 30 school districts in Minnesota to improve their arts education programs. Each district formed a community-based team of eight persons. Each team was then responsible for planning developing, and promoting comprehensive arts education within the district. Following a brief introductory section, this evaluation report provides a program description with information about goals and objectives, the CAPP Steering Committee, foundation grants received, selection and funding, location of projects, use of the teaming concept, and CAPP training and technical assistance. The third section outlines program evaluation objectives and techniques. Findings in section IV are organized around major evaluation questions and deal with 12 major types of CAPP activities, the extent to which the CAPP plan has been implemented, the success of the team approach, helpfulness of training and technical assistance, and major benefits and drawbacks of CAPP. Recommendations for the program, which are summarized in the final section, include continued funding of the arts. Also encouraged was the development of a state-wide clearinghouse which could serve as an information center to establish a network of CAPP programs, to make resources and materials available, to provide training/inservice for various audiences about the arts and CAPP, and to encourage media attention to the arts in general and CAPP programs in particular. At the district level, CAPP districts recognized the need for continued school and community awareness activities, district administrative support, and concern for the composition of the CAPP committee. The committee member questionnaire and the team chair questionnaire are appended. (LH)
ERIC Note: For related document, see SO 016 911.
Policymakers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Art Education; Committees; Educational Needs; Elementary Secondary Education; Fine Arts; Planning; Program Descriptions; Program Development; Program Effectiveness; Program Evaluation; State Programs; Statewide Planning; Team Training; Technical Assistance; Minnesota; Reports, Evaluative